The will to baroque and the dynamics of fine pottery ornamentation of ISPC of carpathian-dniester region - A. A. Romanchuk (Концепт: философия, религия, культура, 2020)
Starting from some ideas of H. Wolflin, O. Spengler pointed out an interesting problem of correlation between the evolution of art and social evolution. Regardless of the realness of their observations and conclusions, the idea of searching and analyzing such correlations seems to be very fruitful, and especially in the context of preliterate culture surviving due to archeology. This paper, drawing on the empirical archaeological data related to so called Incised and Stamped Pottery Cultures (ISPC) of Early Hallstatt period (XII-IX centuries BC) of Carpathian-Dniester region, aims to consider and verify the ideas of H. Wolflin and O. Spengler. For this purpose, and basing on the previously established by the author fivephase evolution scheme of ISPC of Carpathian-Dniester region (including such a key component of ISPC as Sakharna-Soloncheni culture), the dynamic of fine pottery ornamentation of these societies is analyzed. The analysis demonstrates that the evolution of pottery ornamentation of ISPC started from a minimal number of ornamental patterns and moved towards increasing their number. The parallel tendency was the increasing of the ornamented square of pots. These processes, as well as the innovativeness and openness to external influences, peaked in the fourth phase of Sakharna-Soloncheni culture; this phase was also the time of its greatest prosperity.